A BASE NACIONAL COMUM CURRICULAR COMO INDUTORA DAS POLÍTICAS DOCENTES: ANÁLISE DA RESOLUÇÃO CNE/CP Nº 02 DE 2019 E PARECER CNE/CP Nº 22/2019 - XER, Solayne Pereira Freitas,; MILITÃO, Andréia Nunes, (ANAIS DO ENIC, 2023)
-